(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The toxicity of the sediments detected in the northern bays of Lake Onego is determined by anthropogenic factors (pulp-and-paper industry and communal waste waters). Besides the toxic bottom sediments were observed in the central deep part of Lake Onego, which is connected to the geotectonic features of the area.